A temporal perspective on teams - Abrantes, A.; O’Neill, T; Passos, A. M. (Handbook on the Temporal Dynamics of Organizational Behavior, 2020)
Teams are dynamic and temporally determined entities that escape the immutability of a static analysis. Although temporality has always been intrinsically present in team research, traditional methods fail to capture the emergent phenomena of team development over time. Alternative methods must be developed to truly grasp the dynamic nature of teams. In this chapter we discuss the main aspects related to the study of teams from a temporal perspective. We analyze time and its progressive integration in team research, examine the different ways in which temporal issues can be integrated into the team literature, and highlight future research avenues that we hope will encourage team researchers to pursue a time-informed line of research.